INTEGRATION OF PSYCHOLOGY AND LITERATURE AS A MEANS OF DEVELOPING EMOTIONAL INTELLIGENCE IN SCHOOLCHILDREN (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the potential of an interdisciplinary approach to education that combines literary studies with psychological techniques as an effective tool for developing emotional intelligence in schoolchildren. It highlights the theoretical foundations of emotional intelligence, analyzes the impact of fiction on the emotional sphere of the individual, and describes specific methods aimed at fostering empathy, reflection, and the ability to regulate emotions.